2004
DOI: 10.1111/j.1651-2227.2004.tb02751.x
|View full text |Cite
|
Sign up to set email alerts
|

The fifty percent male excess of infant respiratory mortality

Abstract: Aim: To test whether infant mortality from clearly respiratory causes has a consistent male excess that is different from the male excess in most cardiac conditions. Methods: Analysis of male excess in infant mortality data from the United States and from north European countries. Data are analyzed for the period 1979–2002 in autopsied and unautopsied cohorts. Results: Several modes of respiratory death in infancy are characterized by an approximate 50% male excess. This common excess is demonstrated in vital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 12 publications
5
27
0
1
Order By: Relevance
“…Thus, if a genetic marker is present, there is no way to discern whether the infant died of SIDS with LQTS susceptibility or from SCD by LQTS. (2) Universally, SIDS has approximately a 50 % male excess corresponding to a male fraction of about 0.60 for all races combined [2]. However, Stramba-Badiale et al [3] have shown ''that gender-related differences in QTc observed in the adult population are not present at birth''.…”
mentioning
confidence: 99%
“…Thus, if a genetic marker is present, there is no way to discern whether the infant died of SIDS with LQTS susceptibility or from SCD by LQTS. (2) Universally, SIDS has approximately a 50 % male excess corresponding to a male fraction of about 0.60 for all races combined [2]. However, Stramba-Badiale et al [3] have shown ''that gender-related differences in QTc observed in the adult population are not present at birth''.…”
mentioning
confidence: 99%
“…The decline in deaths from infection is likely to affect males and females differently. Because females have more vigorous immune responses and greater resistance to infection (11), female infants have lower mortality from infections (12) and respiratory ailments (13). The male disadvantage begins in utero (14), when gonadal steroid production already differs strongly by sex.…”
mentioning
confidence: 99%
“…We have shown previously that: 1) SIDS cannot be a cardiac death, because SIDS has a constant 50% male excess and cardiac infant deaths have a 0% male excess [1][2][3]; 2) SIDS is not likely to be caused by a brainstem-abnormality because SIDS ages have a lognormal age distribution, sparing infants at or shortly after birth, whereas infants born with fatal neurological defects have maximum mortality shortly after birth [4][5][6]. Rather, we show that SIDS have the same gender distribution (50% excess male rate) as infant deaths from respiratory infection [5,7] and a similar 4-parameter lognormal age distribution as with hospital admissions for bronchiolitis [7].…”
Section: Introductionmentioning
confidence: 99%